Contrasting copper and chromium metallogenic evolution of terranes in the Palaeoproterozoic Itabuna-Salvador-Curaca orogen, Sao Francisco craton, Brazil: new zircon (SHRIMP) and Sm-Nd (model) ages and their significance for orogen-parallel escape tectonics - Oliveira, E.; Windley, B.; McNaughton, Neal; Pimental, M.; Fletcher, Ian (Elsevier Science BV, 2004)
The northern segment of the Palaeoproterozoic Itabuna-Salvador-Cura collisional orogen in the Sao Francisco craton (Brazil) comprises two high-grade terranes separated by the 150 km long, N-S-trending Itiba Syenite. The Cura terrane to the west contains copper sulphide deposits hosted by hypersthenite-norite complexes (e.g. Caraiba body), whereas the Jacurici terrane to the east contains chromite deposits hosted by peridotite-norite sills (e.g. Medrado body). SHRIMP U-Pb dating of zircons, combined with a significant major element compositional gap indicates that the Caraiba (2580±10 Ma) and the Medrado (2085±5 Ma) mafic-ultramafic complexes are not related by fractional crystallisation as previously thought. Depleted-mantle Nd model ages for the regional gneisses are also distinct, with the Cura terrane having younger ages (2.4-2.8 Ga) than the Jacurici terrane (2.9-3.2 Ga), suggesting that they represent two independent fragments of continental crust accreted during the Palaeoproterozoic orogeny. Emplacements of the Itiba Syenite (ca. 2084 Ma) and of the Medrado complex were apparently coeval, probably controlled by orogen-parallel block displacement, or escape tectonics, following continent-continent collision.